Effect of Customer Value and Satisfaction on Customer Loyalty: Evidence on Indonesian Islamic Bank - Rifaatul Indana (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2020)
Given the importance of perceived value and high satisfaction for companies in creating loyalty to achieve their goals and to empirically prove testing, the researchers formulated the problem in research specifically: (1) Does perceived value have an influence on customer loyalty, (2) Does satisfaction affect customer loyalty?. This study uses a Structural Equation Modeling (SEM) approach which is carried out through AMOS software. This research was conducted by utilizing community surveys with online questionnaire. The Sample of this research is 150 respondents, majority of respondents came from the provinces of Central Java and the Special Region of Yogyakarta. Based on the results of the analysis show: customer value has a positive effect on customer satisfaction (CR = 2.492, P = 0.019, H1 supported), customer value has a positive effect on customer loyalty (CR = 2.53, P = 0.026, H2 supported), customer satisfaction has a positive effect on customer loyalty (C.R. = 3.521, P = 0.000, H3 supported). Satisfaction are in a position to create a positive response to the creation of services for consumers, furthermore perceived value plays an important role in representing various client needs and company satisfaction, in the right preferences.